Resilience and Happiness: Impact of Negative and Positive Events on Adolescents - González Arratia López Fuentes, Norma Ivonne; Valdez Medina, José Luis (Pensando Psicología, 2013)
A retrospective study was carried out among adolescents to identify differences in resilience among men and women and their relationship to happiness, after having gone through both positive and negative events in the recent past and which are referred to by the participants. 100 adolescent men and women between the ages of 15 and 19 took part in the study, applying the resilience for adolescents questionnaire (González-Arratia, 2011), the happiness scale (Alarcón, 2006) and the Corsini scale (2004). The results show that there are no significant differences between men and women. A positive relationship is reported between the variables for resilience and happiness. Negative effects have an effect on resilience whereas positive ones favorite. The conclusion is that further analysis of these variables is needed in order to obtain consistent responses.
Keywords: teens; happiness; negative events; positive events; resilience